Determination of Bycatch and Discard Catch Rates on Shrimp Net Fishing in Adana Yumurtalık - Hasan Hüseyin Atar; Koray Tuçdan (Journal of Agricultural Sciences)
In this study which was carried on by Yumurtalık district of Adana province, by catching with the shrimp net, marketable and discarded part of the catch, such as shrimp and other species were investigated. In the area, samples of catch were taken in April, May, June, July, August and September 2004 by fortnight periods. Investigated 3513 species in April- September 2004 was consisted of 1017 shrimps, 1307 bycatch species and 1189 discard species. It was founded that as a weight share of target species from the total catch 19.94%, share of bycatch 40.17%. share of discard 39.89%. In total catch quantitative percentage of target species 28.94%. as a share of bycatch 37.20% and as a share of discard catch 33.86% were calculated. Considering catch per unit (100 m) effort; target species, shrimps as 105.61±16.29 g, bycatch species as 207.26±76.34 g, discard catch as 219.88±176.74 g were determined. Relations as weight between bycatch and discard, target species and bycatch, target species and discard were found significant (P<0.05). When evaluated by quantitative, the relations between target species and discard catch, target species and bycatch, bycatch and discard catch were determined significant (P<0.05).